Comparative Efficacy of Diode, Nd:YAG and Er:YAG Lasers Accompanied by Fluoride in Dentinal Tubule Obstruction: Diode, Nd:YAG and Er:YAG Lasers in Tubule Obstruction - Aghayan, Shabnam; Fallah , Samaneh; Chiniforush, Nasim (Journal of Lasers in Medical Sciences, 2021)
Introduction: Recently, the management of dentin hypersensitivity by lasers has gained special attention. This study aimed to assess and compare the efficacy of the 980 nm diode, Nd: YAG, and Er: YAG lasers accompanied by fluoride in dentinal tubule obstruction. Methods: Twenty sound single-rooted human teeth were used for this in-vitro study. Forty dentinal discs were prepared of the roots and etched with 6% citric acid. One layer of fluoride varnish was applied over their surface. The sections were randomly allocated into 4 groups. The control group received no laser irradiation. Group 2 underwent 980 nm diode laser irradiation with 0.5 W power. Group 3 underwent Nd: YAG laser irradiation with 0.5 W power and group 4 underwent Er: YAG laser irradiation with 0.5 W power. All samples were then inspected under a scanning electron microscope, and the number of obstructed dentinal tubules and the diameter of open dentinal tubules in the field were determined. One-way ANOVA and Tukey’s test were used for data analysis at a significance level of 0.05. Results: All three laser types decreased the number of open dentinal tubules significantly compared to the control group (P<0.05). No significant difference was noted in dentinal tubule obstruction between the three laser groups (P>0.05). The diameter of open tubules in the three laser groups did not show a significant difference from that in the control group. Conclusion: All three types of lasers evaluated in this study can effectively obstruct the dentinal tubules. DOI:10.34172/jlms.2021.63